2021
DOI: 10.3390/children8121126
|View full text |Cite
|
Sign up to set email alerts
|

Towards Consensus on Good Practices for the Use of New Technologies for Intervention and Support in Developmental Dyslexia: A Delphi Study Conducted among Italian Specialized Professionals

Abstract: The use of new technologies for intervention in developmental dyslexia is steadily growing. In order to better understand the needs, the expectations, and the attitudes of Italian expert health professionals concerning such technologies, a national survey was conducted applying the Delphi methodology. Ad-hoc questionnaires were sent out to a group of eighteen experts over three successive rounds, and anonymously collected responses were aggregated and shared with the group after each round, aiming to reach a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Nonetheless, the results provide some important insights on the use of ICT and digital tools in reading interventions. Firstly, our tool was easily integrated both in the face-to-face and in the remote intervention phases, following the guidelines for best practices in the use of ICT in intervention in reading disabilities (Lorusso et al, 2021). Specifically, the parents were involved in the intervention sessions and granted access to the digital tool.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the results provide some important insights on the use of ICT and digital tools in reading interventions. Firstly, our tool was easily integrated both in the face-to-face and in the remote intervention phases, following the guidelines for best practices in the use of ICT in intervention in reading disabilities (Lorusso et al, 2021). Specifically, the parents were involved in the intervention sessions and granted access to the digital tool.…”
Section: Discussionmentioning
confidence: 99%
“…This proliferation of technology in the intervention in reading disabilities has been accompanied by a concern of how they should be employed to maximize the likelihood of positive outcomes. A recent Delphi study aiming to gather guidelines for good practices in the use of technologies for intervention in dyslexia (Lorusso et al, 2021) suggested an overall positive attitude toward the use of ICTbased interventions, with the flexibility, engagement, and costeffectiveness being pointed out as some of the advantages of the format. Moreover, the 18 experts involved in this study provided some insights on best practices: (a) the intervention should be started before the third grade and should last up to 6 months; (b) the intervention should target phonological awareness, visual abilities, lexical skills, and grapheme-to-phoneme conversion; and (c) the families' compliance and their ability to support the children and to mediate and supervise the completion of ICT-based activities should be considered (Lorusso et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The papers included in this Special Issue offer the opportunity to explore this topic from different perspectives as they are focused not only on the efficacy of interventions mediated by technology [1][2][3] but also on the impact that the use of technology in telerehabilitation, in particular during the COVID-19 pandemic, has had on wellbeing experience of children with Specific Learning Disorders and Cerebral Palsy [4]. Moreover, due to the relevance of the use of technology in the treatment of Specific Learning Disorders, Lorusso et al [5] carried out a Delphi study to propose a set of best practices in order to guide the use of technology to realize training programs and to support learning processes in school activities.…”
mentioning
confidence: 99%
“…As the role of technology and telerehabilitation has been rising during the last decade and is likely to increase in the future, it might be important to identify the best practices that can provide professionals with suggestions and share experience among practitioners in order to offer effective support to the greatest number of children in any condition of implementation of the treatment. The paper by Lorusso et al [5] presents a synthesis of a Delphy study conducted among Italian professionals, aiming to endorse some statements on the use of new technologies applied in the treatments of Dyslexia, which will be included within a European project on the use of VR and AR in learning to read. Overall, the respondents showed a positive attitude towards the use of Information and Communication Technology in rehabilitation programs and appreciated, in particular, the application of VR in training programs aimed at the automation of grapheme-to-phoneme conversion rules.…”
mentioning
confidence: 99%